Implementation of the “Maghrib Mengaji” Program as a Medium for Early Childhood Qur’an Learning - Widaningsih Widaningsih; Luthfiah Nur Istighna; Gilang Arival Mulyandika; Hanny Anisa Amalia (Indonesian Journal of Research in Islamic Studies, 2025)
Background: The Maghrib Mengaji program has long been a Muslim tradition that fosters Qur’anic literacy and moral development. Its continued existence plays a vital role in strengthening community-based religious education, particularly for young children. Objective: This study aims to describe the implementation of the Maghrib Mengaji program as a medium for Qur’an learning among early childhood students. Method: A qualitative descriptive approach was used, with the research conducted at TPQ Al Ittihad, Cirebon Regency. Data were collected through observation and interviews with program organizers and participants. Result: The findings reveal insights into the history and implementation of the Maghrib Mengaji program, its roles and benefits for early childhood Qur’an learning, and the obstacles encountered during its execution. Conclusion: The Maghrib Mengaji program serves as an effective platform for introducing Qur’anic learning and strengthening children’s spiritual values. However, challenges such as limited resources and scheduling conflicts remain to be addressed. Contribution: This study contributes to the understanding of community-based Islamic education and provides a framework for improving Qur’anic learning strategies for early childhood through the Maghrib Mengaji tradition.